25 The effects of closely meeting estimated daily lysine and energy requirements for pregnant sows across two pregnancies on sow body weight change and litter characteristics at birth. (30th November 2020) - Stewart, Victoria; Hansen, Lauren; Mandell, Ira; Huber, Lee-Anne
Abstract: Gestating sows experience varying nutrient and energy requirements throughout gestation and across parities. The objective of the current study was to determine the effects of precisely meeting estimated (daily) energy and Lys requirements for gestating sows over two pregnancies on sow body weight (BW) change and litter characteristics at birth. One hundred and seven sows (average parity 1.4±0.5) were randomly assigned to a precision (PF ; n=52) or control (CON ; n=55) feeding program between day 2 and 9 of gestation and housed in group-pens equipped with electronic sow feeders capable of blending two diets. The PF sows received unique daily blends of two isocaloric diets (2518 kcal/kg NE; 0.80 and 0.20% SID Lys, respectively) while the CON sows received 2.2 kg of a static blend of the dietsto achieve 0.56% SID Lys throughout gestation. After weaning, sows were re-bred and entered the same feeding program as in the previous pregnancy (PF: n=37; CON: n=37; average parity 2.4±0.5). During the first pregnancy, CON sows had greater BW gain in the first trimester (15.1 vs 10.2±1.2kg; P < 0.05), but BW at the end of gestation did not differ. In the second pregnancy, PF sows had a greater BW gain in the second (21.4 vs 14.1±1.7kg; P < 0.05) and third trimesters (32.6 vs 24.7±3.1 kg; P < 0.05), along with heavier BW and greater loin depths at the end of gestation (249.1 vs 232.9±5.6kg and 73.1 vs 70.4±1.1mm, respectively; P < 0.05). The number of piglets born alive, stillborn, and mummified, and litter birth weights did not differ in either pregnancy. Precision feeding of gestating sows reduced BW gain in the first trimester of the first pregnancy and increased BW gain and maternal protein stores (i.e. loin depth) in the subsequent pregnancy, without affecting litter characteristics at birth.